Evaluation of Preventive Role of Systemically Applied Erythropoietin after Tooth Extraction in a Bisphosphonate-Induced MRONJ Model - Gonca Duygu; Gül Merve Yalcin-Ülker; Murat Günbatan; Merva Soluk-Tekkesin; Ceyda Özcakir-Tomruk (Medicina, 2023)
Background and Objectives: In this experimental study, the prophylactic effect of systemically administered erythropoietin (EPO) in medication-related osteonecrosis of the jaw (MRONJ) was evaluated. Materials and Methods: The osteonecrosis model was established using 36 Sprague Dawley rats. EPO was systemically applied before and/or after tooth extraction. Groups were formed based on the application time. All samples were evaluated histologically, histomorphometrically, and immunohistochemically. A statistically significant difference in new bone formation was observed between the groups (p < 0.001). Results: When new bone-formation rates were compared, no significant differences were observed between the control group and the EPO, ZA+PostEPO, and ZA+Pre-PostEPO groups (p = 1, 0.402, and 1, respectively); however, this rate was significantly lower in the ZA+PreEPO group (p = 0.021). No significant differences in new bone formation were observed between the ZA+PostEPO and ZA+PreEPO groups (p = 1); however, this rate was significantly higher in the ZA+Pre-PostEPO group (p = 0.009). The ZA+Pre-PostEPO group demonstrated significantly higher intensity level in VEGF protein expression than the other groups (p < 0.001). Conclusions: Administering EPO two weeks pre-extraction and continuing EPO treatment for three weeks post-extraction in ZA-treated rats optimized the inflammatory reaction, increased angiogenesis by inducing VEGF, and positively affected bone healing. Further studies are needed to determine the exact durations and doses.